EFFECT OF FLUID VELOCITY ON THE THERMAL EFFICIENCY OF A SHELL AND TUBE HEAT EXCHANGER THROUGH A COMPUTATIONAL FLUID DYNAMIC (CFD) APPROACH - Iksan Arif Munandar; Ryan Sadewo (Trends in Mechanical Engineering Research, 2026)
Heat exchanger efficiency is critical in industrial energy management. The relationship between fluid velocity and thermal performance in shell and tube heat exchangers (STHE) remains insufficiently quantified in an integrated ther-mo-hydraulic framework. This study investigates the effect of fluid velocity (0.5–2.5 m/s) on STHE thermal efficiency using Computational Fluid Dynamics (CFD) with the k-ω SST turbulence model, grounded in the Dittus-Boelter correlation, Darcy-Weisbach equation, and ε-NTU method. A three-dimensional geometry (shell diameter 380 mm, 104 tubes, 6 baffles) was simulated in ANSYS Fluent 2023 R1 using 1.8 million mesh elements, validated against the Bell-Delaware analytical method and experimental data from Sutoyo et al. (2024), with a maximum deviation of 6.3%. Results show that the overall heat transfer coeffi-cient increased sub-linearly from 1,245 to 2,087 W/m²· K, while pressure drop grew quadratically from 2,180 to 14,520 Pa. Thermal efficiency rose from 62.4% to 80.3% but exhibited saturation at higher velocities. The Performance Evalua-tion Criteria (PEC) peaked at 1.31 for v = 1.5 m/s, identifying this as the optimal operating condition with 76.5% thermal efficiency and manageable pressure losses. These findings confirm that v = 1.5 m/s represents the best thermo-hydraulic balance and provide practical guidance for energy-efficient STHE operation in industrial applications.